Student’s Perception and Preference of Food Package Design: A Pilot Project - Wirania Swasty; Mohammad Isa Pramana Koesoemadinata; Ahmad Nur Sheha Gunawan; Mediany Kriseka Putri (Institute of Research and Community Outreach - Petra Christian University, 2018)
The food home industry in Bandung is increased by 7.19 percent in 2017. However, the lack of attractive packaging makes them not competitive in the market. A deep understanding of packaging and labeling is important. This research’s objective is to contribute to the development of packaging design especially the food home industry products and also can be used as a reference for further research related to color perception, packaging design, and the creative industry. This study uses a qualitative and quantitative approach. Data collection is done through literature study, market observation, and questionnaires. This study is a pilot study for further research on the correlation between the perception of color combinations and consumer preferences. The results become the foundation for designing the Primary Display Panel of the banana chips home industry. From the study, it is suggested that the price that consumers perceive against the banana chips brands is the same as the actual price on the market